Multilevel research: Foundations and opportunities in management. Issue 4 (October 2020) - Molina-Azorín, José F; Pereira-Moliner, Jorge; López-Gamero, María D; Pertusa-Ortega, Eva M; José Tarí, Juan
The purpose of this methodological insight is to analyze the foundations of multilevel research, answering two main questions: why this methodological approach is important for management research and how to conduct a multilevel study. We examine why multilevel research is relevant, emphasizing its potential, opportunities, and basic principles. Moreover, we point out the main theoretical, methodological, and analytic aspects to be considered for an appropriate application of multilevel research. The article refers throughout to the basic literature on multilevel research, reviewing conceptual, methodological, and empirical works. JEL CLASSIFICATION: C18; M10